Relationship Of Self-Acceptance With Quality Of Life In Chronic Kidney Failure Patients - Cut Mutia Zuhra; Zurratul Muna (Faculty of Medicine University of Malikussaleh, 2022)
This study aims to see whether there is a relationship between self-acceptance and quality of life in patients with chronic kidney failure. This study uses a quantitative approach with a random sampling technique. The research subjects were 130 people with chronic kidney failure. The data collection method used a self-acceptance scale that was compiled by the researcher himself based on the aspect of self-acceptance from Bernard which consisted of 39 items and the quality of life scale which was compiled by the researcher himself based on the quality of life aspect of Sirgy which consisted of 29 items. Data analysis using Product Moment correlation technique. The relationship between self-acceptance variables and quality of life in patients with chronic kidney failure is accepted. This means that the higher the self-acceptance of patients with chronic kidney failure, the higher their quality of life. Conversely, the lower the self-acceptance of patients with chronic kidney failure, the lower their quality of life